Past, Present, and Future of Forbs in Old-Growth Tropical and Subtropical Grasslands - Siebert, Frances; te Beest, Mariska; Fynn, Richard; Klimešová, Jitka; Morris, Craig; Nkuna, Sindiso; Siebert, Stefan; Fidelis, Alessandra [UNESP] (Annual Reviews, 2024)
Forbs are important contributors to species diversity and ecosystem functions in low-latitude grasslands, where they support diverse herbivore communities and millions of people. Native forb assemblages tolerate disturbances and physiological stressors (fire, herbivory, drought, and frost) that together have shaped their exceptional functional diversity. Yet, compared to trees and grasses, forbs have received much less attention in grassland studies until recently. Here, we review forb-centric literature to illustrate that land conversion and responsible management of fire and herbivory are crucial to maintaining forb diversity. Management practices promoting forb diversity offer (a) high-quality food items and medicinal resources that support rural livelihoods and animal diversity (from wild ungulates and livestock to fossorial rodents and insects), including their adaptive foraging patterns, and (b) carbon and nutrient inputs that regulate belowground processes. Improved understanding of the above- and belowground regeneration strategies of forbs is critical for restoration and conservation to secure their services in future old-growth tropical and subtropical grasslands.
Keywords: belowground functional diversity; ecosystem services; fire; foraging; herbivory; medicinal plants; underground storage organs